Video calls from lay bystanders to dispatch centers - risk assessment of information security - Hasvold Per; Bolle Stein R; Henriksen Eva (BMC Health Services Research, 2011)
Abstract Background Video calls from mobile phones can improve communication during medical emergencies. Lay bystanders can be instructed and supervised by health professionals at Emergency Medical Communication Centers. Before implementation of video mobile calls in emergencies, issues of information security should be addressed. Methods Information security was assessed for risk, based on the information security standard ISO/IEC 27005:2008. A multi-professional team used structured brainstorming to find threats to the information security aspects confidentiality, quality, integrity, and availability. Results Twenty security threats of different risk levels were identified and analyzed. Solutions were proposed to reduce the risk level. Conclusions Given proper implementation, we found no risks to information security that would advocate against the use of video calls between lay bystanders and Emergency Medical Communication Centers. The identified threats should be used as input to formal requirements when planning and implementing video calls from mobile phones for these call centers.